Визначення оптимального шляху транспортних потоків та прогнозування дорожніх заторiв за допомогою штучного інтелекту - Гнилицький, Я. В. (ХНУРЕ, 2022)
Traffic congestion reduces the efficiency of road networks. The decline in efficiency leads to direct and indirect costs to society such as reduced working hours or environmental pollution. The purpose of the report is to develop a system that allows you to prevent traffic jams through artificial intelligence. The possibility of using it on city roads by using cameras installed next to traffic lights.